2020
DOI: 10.3389/fimmu.2020.01917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Influenza Vaccination Inducing Antibody Mediated Rejection in Solid Organ Transplant Recipients

Abstract: Introduction Our goal was to study whether influenza vaccination induced antibody mediated rejection in a large cohort of solid organ transplant recipients (SOTR). Methods Serum anti-Human Leukocyte Antigen (HLA) antibodies were determined using class I and class II antibody-coated latex beads (FlowPRA TM Screening Test) by flow cytometry. Anti-HLA antibody specificity was determined using the single-antigen bead flow cytometry (SAFC) assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…In keeping with these findings, NA-GMT in liver transplant recipients was significantly higher than that in kidney and heart transplant recipients. The degree of immunosuppression for SOT recipients is based on risk assessment for rejection [23] versus infection and is determined by multiple factors, such as the transplant type, degree of sensitization to human leukocyte antigens, prior allograft rejection, age, and comorbidities. The lower response of heart transplant recipients was not related to age, as those patients were not older than the kidney or liver transplant subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with these findings, NA-GMT in liver transplant recipients was significantly higher than that in kidney and heart transplant recipients. The degree of immunosuppression for SOT recipients is based on risk assessment for rejection [23] versus infection and is determined by multiple factors, such as the transplant type, degree of sensitization to human leukocyte antigens, prior allograft rejection, age, and comorbidities. The lower response of heart transplant recipients was not related to age, as those patients were not older than the kidney or liver transplant subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the BNT162b2 mRNA vaccine was safe, without any episode of rejection, GVHD or allergy. While concern has been raised that vaccination might trigger rejection, numerous trials have shown no causal association between vaccination and organ rejection [23] . The immunocompetent controls in our study experienced significantly more AEs than the ICPs.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported 11.9%–17.3% of patients have positive anti‐HLA antibodies following H1N1 vaccination 4 . However, a meta‐analysis 22 and a recent report 23 indicated that the incidences of de novo DSA and rejection after H1N1 vaccination in solid organ transplant recipients were rather low. Several mechanisms have been proposed for the vaccination effects—immune mimic, the adjuvant effect on innate immunity, and bystander activation of quiescent alloreactive memory 24 …”
Section: Discussionmentioning
confidence: 99%
“…3,7,8 While the risks of COVID-19 vaccines in respect to anti-HLA Abs induction is still unclear, it is documented that some vaccines, such as seasonal influenza and pneumococcal vaccines, can be associated with re-stimulating or activating memory B cells that have been previously formed after historical sensitizing events leading to induction of anti-HLA Abs production in solid-organ transplant recipients. [9][10][11] A recent report also showed a possible reactivation of Abs against repeat mismatched class II DR antigen post COVID-19 vaccination. 12 Any change in the anti-HLA Abs pool in potential solid organ transplant recipients can dramatically affect the flow cytometric cross matching (FCXM) and the success of transplants as even low incidences of anti-HLA Abs are shown to induce solid organs rejection.…”
Section: Introductionmentioning
confidence: 94%